2008
DOI: 10.1183/09031936.00004707
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung diseases in infants and children: Fig. 1—

Abstract: Interstitial lung disease (ILD) in infants and children represents a heterogeneous group of respiratory disorders that are mostly chronic and associated with high morbidity and mortality.Typical features of ILD include dyspnoea, the presence of diffuse infiltrates on chest radiographs and abnormal pulmonary function tests with evidence of a restrictive ventilatory defect (in older children) and/or impaired gas exchange.ILD is difficult to diagnose, as no classification scheme is entirely satisfactory. Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 75 publications
(96 reference statements)
0
48
0
18
Order By: Relevance
“…However, their reluctance to perform the analysis was somewhat understandable as there is currently no specific treatment for the lung disease due to SP-C gene mutations. (8) Furthermore, history revealed that no other family members or relatives died from unexplained lung disease or had a life-long history of chronic respiratory problems or atypical asthma. Supposing that neither parent carries the I73T mutation, then it could be a de novo mutational event causing sporadic lung disease in the boy.…”
Section: Discussionmentioning
confidence: 99%
“…However, their reluctance to perform the analysis was somewhat understandable as there is currently no specific treatment for the lung disease due to SP-C gene mutations. (8) Furthermore, history revealed that no other family members or relatives died from unexplained lung disease or had a life-long history of chronic respiratory problems or atypical asthma. Supposing that neither parent carries the I73T mutation, then it could be a de novo mutational event causing sporadic lung disease in the boy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to adult patients, ILD children present a broad spectrum of relatively rare pulmonary disorders featuring persistent inflammatory injures in the lung tissue with altered fibrogenesis [28,30,31]. Disruption in the integrity of the alveolar epithelium occurs with the accumulation and activation of immune cells, proliferation of fibroblasts in addition to reduced apoptosis of endothelial cells and alveolar septal cells [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen children suffered from IIP with worsening lung function and deterioration of alveo-capillary function detected by dynamic inhalative lung scan as described previously [29]. These subjects were histopathologically classified as acute interstitial pneumonia (n = 5), non-specific interstitial pneumonitis (n = 7) or non-classified IIP (n = 4) by open lung biopsy or video-assisted thoracoscopic surgery [30,31]. Finally, three subjects were diagnosed with IPH based on hemoptysis, bilateral bloody bronchial discharge by bronchoscopy and hemosiderin-laden macrophages of >95% in BALF [32].…”
Section: Methodsmentioning
confidence: 99%
“…Известно, что фибробласты продуцируют различные протеазы (урокиназу и коллагеназу), разрушающие межкле-точный матрикс, и ингибиторы матриксного разло-жения (тканевые ингибиторы металлопротеиназ). Секретируя цитокины (ИЛ-6, ИЛ-8, ростовой фак-тор кератиноцитов), фибробласты, в свою очередь, передают сигналы клеткам, участвующим в воспа-лении, эндотелиальным клеткам и альвеолоцитам II типа, активируют или регулируют другие кле-точные взаимодействия, которые также могут при-водить к повреждению легочной ткани [7,8]. При большинстве ИЗЛ наблюдается пролиферация аль-веолоцитов II типа и их миграция в очаг поврежде-ния.…”
Section: резюме в статье представлены литературные данные о распростunclassified